Hoarding symptoms among psychiatric outpatients: confirmatory factor analysis and psychometric properties of the Saving Inventory – Revised (SI-R). Issue 1 (December 2016) - Lee, Siau Pheng; Ong, Clarissa; Sagayadevan, Vathsala; Ong, Rebecca; Abdin, Edimansyah; Lim, Susan; Vaingankar, Janhavi; Picco, Louisa; Verma, Swapna; Chong, Siow; Subramaniam, Mythily
Abstract Background The growing interest in problematic hoarding as an independent clinical condition has led to the development of the Saving Inventory-Revised (SI-R) to assess hoarding phenomenology. The SI-R is one of the most widely used instruments to measure hoarding symptoms; however, it lacks validation in non-Western samples. Methods The current study examined the construct, convergent, and discriminant validity of the SI-R among 500 outpatients at a psychiatric hospital in Singapore. The three-factor structure solution of the SI-R was fitted in a confirmatory factor analysis. Results The final model achieved mediocre fit (χ 2 = 1026.02, df = 186; RMSEA = 0.095, SRMR = 0.06; CFI = 0.86; NNFI = 0.85). Two reverse-coded items (items 2 and 4) were removed due to insufficient factor loadings, resulting in the modified 21-item SI-R (SIR-21). Our findings indicate the need to further examine the construct validity of the SI-R, particularly in non-Western samples. Nonetheless, correlations with other hoarding-related constructs, such as anxiety (Beck Anxiety Inventory) and depression (Beck Depression Inventory-II), supported the convergent and discriminant validity of the SIR-21 in our sample. Conclusions Findings in our current majority Chinese sample were consistent with previous observations from other Chinese samples. Implications were discussed from a cross-cultural perspective, such as cultural emphasis on saving for future use and overlap between the concepts of discarding and acquiring in Chinese samples. Future studies should also examine differences among other ethnic groups (e.g., Malay, Indian).